Mutation c.256_257delAA in RAG1 Gene in Polish Children with Severe Combined Immunodeficiency: Diversity of Clinical Manifestations - Szaflarska, Anna (Arch Immunol Ther Exp (Warsz), 2017)
Mutations in RAG1 gene may result in different types of severe combined immunodeficiencies. In this study, we compare clinical symptoms and laboratory findings in four children with identical mutation in RAG1 gene. All of analyzed patients presented symptoms of severe combined immunodeficiencies associated or not with Omenn syndrome (OS) features. In our patients two different types of variants in RAG1 gene were detected. The first of the mutation was the deletion of AA dinucleotide at position c.256_257 (p.Lys86ValfsTer33), the second gene variant was substitution c.2867T>C (p.Ile956Thr). In Patient 1 we detected that compound heterozygous mutations involved both of the mentioned variants. Whereas, in Patients 2, 3 and 4, we confirmed the presence of the dinucleotide deletion but in a homozygous state. In all described patients, sequence analysis of RAG2 gene did not reveal any nucleotide changes. Our data show that mutation c.256_257delAA in RAG1 gene seems to occur quite frequently in the polish patients with severe combined immunodeficiency and may result in classical OS as well as in severe combined immunodeficiency without clinical and laboratory features of OS when occurred in homozygous state. The same mutation but in heterozygous state, in combination with other mutation in RAG1 gene, may result in incomplete OS.